2008
DOI: 10.1071/ea07426
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance and implications for future aphid management in Australian grains and pastures: a review

Abstract: Aphids can cause substantial damage to cereals, oilseeds and legumes through direct feeding and through the transmission of plant pathogenic viruses. Aphid-resistant varieties are only available for a limited number of crops. In Australia, growers often use prophylactic sprays to control aphids, but this strategy can lead to non-target effects and the development of insecticide resistance. Insecticide resistance is a problem in one aphid pest of Australian grains in Australia, the green peach aphid (Myzus pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…Subsequently, Herron et al (1993) reported organophosphate resistance levels (40-fold) and low-levels of tolerance to carbamates (20-fold) in M. persicae populations from stone fruit. A 2005 survey of M. persicae across the grain growing regions of Australia found ampliÞed E4 esterase conferring resistance to organophosphates in almost every aphid sampled (Edwards et al 2008). The same survey identiÞed knockdown resistance (kdr) to synthetic pyrethroids present in 25Ð100% of aphids sampled, with the frequency increasing in vegetable growing regions (Edwards et al 2008).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequently, Herron et al (1993) reported organophosphate resistance levels (40-fold) and low-levels of tolerance to carbamates (20-fold) in M. persicae populations from stone fruit. A 2005 survey of M. persicae across the grain growing regions of Australia found ampliÞed E4 esterase conferring resistance to organophosphates in almost every aphid sampled (Edwards et al 2008). The same survey identiÞed knockdown resistance (kdr) to synthetic pyrethroids present in 25Ð100% of aphids sampled, with the frequency increasing in vegetable growing regions (Edwards et al 2008).…”
mentioning
confidence: 96%
“…In Australia, M. persicae are now extensively targeted with insecticides in oilseeds, pulses, and vegetable crops (Edwards et al 2008). Heavy reliance on insecticides to manage aphid populations places strong selection pressure to develop resistance, and M. persicae has probably developed resistance to more insecticides than any other insect species (Caillaud et al 2004, Whalon et al 2008).…”
mentioning
confidence: 98%
“…The current action threshold for cabbage aphids in canola is a function of proportion of plants infested (i.e., 20%). Furthermore, the spatial distribution of cabbage aphids in canola fields, relative to field edges, has been more accurately modeled using presence/absence of cabbage aphids on plants, rather than cabbage aphid counts or colony lengths on racemes; this further supports the use of binomial rather than count data in the development of a sampling plan (Edwards et al 2008, Severtson et al 2015.…”
Section: Discussionmentioning
confidence: 64%
“…During the widespread adoption of canola cultivation in Australia in the late 1990s (Salisbury 1999), an action threshold of 100% of sampled canola plants infested with at least 0.5 cm of cabbage aphid colony length on racemes was suggested as an action threshold, because economic damage by cabbage aphids was difficult to demonstrate in experimental field trials (Berlandier 2000(Berlandier , 2002Berlandier and Valentine 2003). In 2004, and as a result of further research, an action threshold of 20% of plants infested with cabbage aphids (especially in low rainfall regions) was suggested and has since been recommended in canola-producing regions of Australia (Berlandier 2004, Edwards et al 2008, Bellati et al 2010, Berlandier et al 2010. The current number of samples recommended to estimate aphid infestation levels in canola in Australia is a minimum of 20 plants selected at random and inspected at each of at least 5 points throughout a field (Bellati et al 2010).…”
Section: Action Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation